Effect of nanoclay and silica aerogel on mechanical, thermal and physical properties of sugar palm fibre- reinforced unsaturated polyester composites - Shahroze Ali, Rao Muhammad (2018)
With the increasing rate of technological developments, the use of specialized materials, such as composites, is continuously increasing. Conventional composites are prepared from synthetic raw materials which are proving to be hazardous to the environment and measures need to be taken to reduce their effects on the environment. Reinforcing natural fibres in composites is a potentially viable solution to this problem and can result in enhanced properties as well. Sugar palm fibres are also anticipated to be used in a similar scope, however, there is a need for improvement in properties before they can be successfully employed in relevant applications. This study focused on enhancing the usability of Sugar palm fibre in polymer composite with the addition of fillers. This study investigated the effect of filler loading on sugar palm fibre reinforced unsaturated polyester composite. Naturally existing woven sugar palm fibres were used in this study as reinforcement and unsaturated polyester was used as the matrix. Nano-fillers namely, nanoclay and silica aerogel were infused in the sugar palm fibre reinforced polyester composite. Composites were prepared with hand layup process followed by the hydraulic hot press, which pressed the mould for 30 minutes at 80 °C. Different weight percentages of nanoclay content (NC) and silica aerogel content (SAC) were used to prepare the composite. The filler loadings of 0, 1, 2, 3, 4 and 5 % were used for both the fillers. Mechanical, thermal and physical tests were performed on the fabricated composites and the results were analysed. Tensile, flexural and impact tests were performed according to respective ASTM standards. Almost all the composites with infused fillers showed higher tensile strength and 4 % NC mixed composite showed the highest tensile strength and modulus improvement of 58 % and 12 % respectively. Flexural properties of nanoclay based composites also showed higher improvement compared to silica aerogel based composites. A 54 % increase in flexural strength and 42 % maximum increase in flexural modulus was achieved with the addition of nano-fillers compared to composite without any filler. Both nanoclay and silica aerogel were able to achieve better and similar impact strength but at different filler loading. 2 % for nanoclay and 3 % for silica aerogel achieved almost 20 % improvement in impact strength compared to 0 % composite. SEM images of the impact fracture composite were discussed and analysed. For thermal analysis, dynamic mechanical analysis (DMA) and thermogravimetric analysis (TGA) were performed. Addition of both the fillers improved the dynamic mechanical and thermal properties of the composite. The optimum concentration for both the fillers to achieve the best thermal performance was found to be between 2 % to 3 %. To determine the physical properties, water absorption and thickness swelling investigation of the composites were carried out. The composites were immersed in distilled water for up to 13 weeks to analyse long-term water absorption and thickness swelling characteristics of the composites. Composites with nanoclay restricted and reduced the moisture uptake and dimensional deformation when immersed in water while silica aerogel infused composites showed higher levels of water absorption and thickness swelling compared to composites without additives. This study concluded that the addition of studied fillers can significantly improve the properties of sugar palm reinforced composites, making it more usable for a broader range of tertiary applications, where currently conventional composites are employed.